Organizing Central Securities Depositories in Developing Markets-7 Considerations - Wendt, Froukelien (IMF Working Papers; Working Paper ;, 2018)
Central securities depositories (CSDs) are systemically important entities that are critical for effective implementation of monetary policy, the credibility of a government's debt management program, collateral management, and safe and efficient securities markets. Authorities in developing markets, in particular central banks, may grapple with the following issues: i) whether to pursue a single CSD for all types of securities to increase market efficiencies and benefit from economies of scale; and ii) whether to partake in the governance of the CSD as owner and/or operator. This paper develops seven considerations that authorities may take into account in addressing these issues and finding the best model for their country. These may point to different solutions for different countries, depending in part on the size of markets, strength of private operators and level of market development.